(untitled) (Praxis Educativa, 2024)
The objective of the article is to problematize the conception of the relationships between the world of work and training. It ends with a ’provisional order’ of knowledge that are mobilized in the various spheres of work(s). The article starts with a brief characterization of the structure of paid work in Argentina, which is the legitimate reference to the knowledge for the work force; secondly, an approach to the diversity of worlds of work (paid, domestic and community) is organized where relationships and ways of knowing in production are developed; in the third step, the tensions between hierarchies of knowledge and production processes are presented whereof, in the following section, the intersections between spheres of work and the crossing of knowledge between them are elaborated; it ends with a provisional ordering of types of knowledge in relation to the different worlds of work.